(3cJGH GdJhGHjfs - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs ((3eMeO Hf YHO Gdhdi Hf CHj eMeO Hf NhdGf GdMfHdi s)
(3ChdgG (B:s
(3eHJhQ GdChd , hjHOC GdehLhO efgG HGH JhHI OGhO Ydjg GdSdGe s
(3BNQgG (B:s
(3hBNQgG eHJhQ CjVkG jfJgi CKfGA HGH PcQ LeGYI eef CSde s
(3HgG SeGY dcGJHgs
(3fSNI KGdKI efgs
(3hGdfSNI HQhGjI GdbGVi JGL GdOjf CHj eMeO YHO GdNGdb Hf YdhGf GdTGaYis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B333 s
Keywords: (3GdJGQjNs